Tujuan Pendidikan Islam - Hj. Mat Diah, Abdul Halim (Jurnal Usuluddin, 1995)
This article tries to portray the importance of Islamic education in building a nation and a state. It guarantees and becomes part of the requirement for development and prosperity.